NINCOMPOOPERY : why your customers hate you - and how to fit it. - Brandt, John R. (Nashville, Tennessee] : Harper Collins Leadership, an imprint of HarperCollins, 2019)
"Nincompoopery -- terrible customer service, idiotic business processes, and soul-crushing management practices -- surrounds all of us. We lose time, patience, and profits as stuck-in-the-past organizations actively prevent us (and our customers) from getting the value we (and they) deserve. Can't anybody change this? CEO and award-winning business writer John R. Brandt says we can. In Nincompoopery: Why Your Customers Hate You -- And How to Fix It, he leverages research across thousands of companies to show leaders how to find and kill the corporate stupidity that drives customers crazy. More importantly, he offers concrete examples of how any organization -- large or small, and regardless of industry -- can innovate in ways that delight customers and attract top-level talent"
Chapter 1. Overview: are we really surrounded by nincompoops? -- Chapter 2. Innovation: what is innovation, anyway? -- Chapter 3. Talent: who's going to do all this stuff? -- Chapter 4. Process: hey, let's talk process! Wait... where are you going? Come back! -- Chapter 5. Getting started: obstacles and opportunities -- Afterword. Nincompoopery macro trends: why is it so ridiculously hard to be a leader these days?
Translated from the Norwegian.
Includes bibliographic references (pages 171-188) and index.
Keywords: Customer relations; Consumer satisfaction; Success in business; Organizational effectiveness; Leadership